The Prehistory of the Operette Morali: Leopardi’s Early Machiavellism or How to Write Usefully - Fazio, Beatrice (Rivista Internazionale di Studi Leopardiani, 2023)
In 1821, a year of significant political events in the slow-moving process of Italian independence, Leopardi identified Machiavelli as the political pendant of those who have «truly changed the face of philosophy », namely Galileo, Descartes, Locke, and Newton. Meanwhile, imbued with a project of literary and social reform, he wrote a series of prosette satiriche in an effort to create a new genre of moral and philosophical satire. As he composed the prosette and prepared the Operette morali, Machiavelli remained an enduring influence. This study explores the internal history of the Machiavelli-Leopardi interaction through an analysis of the Novella Xenophon and Niccolò Machiavello to understand Leopardi’s own reformulation of ‘Machiavellism’ and its historically specific meanings. Rather than an ‘effacement’ of Machiavelli in both the Zibaldone and the Operette morali, I argue that his moral philosophy has fused with Leopardi’s own vision of the relationship between ethics, politics, and the purpose of literature.